Review of Static Compensation of Autonomous Systems - Ambarnath Banerji; Sujit K. Biswas; Bhim Singh (International Journal of Power Electronics and Drive Systems (IJPEDS), 2012)
Deregulation of the electric power energy market has thrown open opportunities for tapping the large number of small pockets of renewable energy sources with the asynchronous generators. Whether the power is supplied by asynchronous generator or by the grid at the remote location, its quality has become an important aspect for consumers of electricity. Efforts have been made to improve the power quality using passive filters, active filters and the new concept of Custom Power. Use of Custom power devices ensures that a load do not pollute the power supply of the other loads. One such custom power device is the DSTATCOM (Distribution Static Compensator) which is connected in shunt at the load end. The heart of the DSTATCOM is an inverter. The focus on the autonomous generation has increased in the recent years. The paper presents a comprehensive review of the DSTATCOM used for autonomous generation. It is aimed at providing a broad perspective on the status of DSTATCOM, used with Asynchronous generators, vis-à-vis its working principle, topology, solid state switching devices and technology, supply system, control methodologies and approaches, technical and economic considerations, etc. to researchers and application engineers dealing with power quality aspects of Autonomous Systems. Classified manner in which the references are presented in this paper will serve them as quick and useful reference.DOI: http://dx.doi.org/10.11591/ijpeds.v2i1.174